2008
DOI: 10.1111/j.1467-7687.2008.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive development of relational reasoning

Abstract: Relational reasoning is an essential component of fluid intelligence, and is known to have a protracted developmental trajectory. To date, little is known about the neural changes that underlie improvements in reasoning ability over development. In this event-related functional magnetic resonance imaging (fMRI) study, children aged 8-12 and adults aged 18-25 performed a relational reasoning task adapted from Raven’s Progressive Matrices. The task included three levels of relational reasoning demands: REL-0, RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
176
1
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(202 citation statements)
references
References 40 publications
(69 reference statements)
20
176
1
3
Order By: Relevance
“…Consistent with this perspective, our group has found that lateral parietal activation during performance of a Raven-like matrix reasoning task scales with the number of relations to be considered [34]. Further, lateral parietal cortex is engaged more strongly when fMRI study participants represent ordered relations (e.g., x is larger than y) than associative relations (e.g., x and y are related) on a test of transitive inference [35] -i.e., when the nature of the relationships must be considered to solve the problem.…”
Section: Neurodevelopment Of Reasoningsupporting
confidence: 58%
“…Consistent with this perspective, our group has found that lateral parietal activation during performance of a Raven-like matrix reasoning task scales with the number of relations to be considered [34]. Further, lateral parietal cortex is engaged more strongly when fMRI study participants represent ordered relations (e.g., x is larger than y) than associative relations (e.g., x and y are related) on a test of transitive inference [35] -i.e., when the nature of the relationships must be considered to solve the problem.…”
Section: Neurodevelopment Of Reasoningsupporting
confidence: 58%
“…Other researchers who have developed their own Raven-like matrix problems have also defined the difficulty of their problems according to the number of rules or relations that must be combined to solve the problem (Arendasy & Sommer, 2005;Christoff et al, 2001;Crone et al, 2009;Green & Kluever, 1992;Halford, Wilson, & Phillips, 1998;Waltz et al, 1999). A zero-relation problem is one in which a matrix contains no changes and the answer is a simple one-to-one match to the shape that is repeated in the matrix.…”
Section: P Smentioning
confidence: 99%
“…No previous study has directly investigated the development of this ability. In children, manipulation of SI thoughts has been studied in the context of fluid intelligence (Wright et al, 2008;Crone et al, 2009) and working memory (WM) tasks (Crone et al, 2006), while the ability to resist distracting SO information has been studied in perceptual (Bunge et al, 2002;Booth et al, 2003) and WM tasks (Olesen et al, 2007). Here, we used a single task that could be performed on the basis of either SO or SI information, without high WM requirements (Gilbert et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%